Produçao do conhecimento em Educaçao Física: Algumas reflexoes a partir do Brasil - Fensterseifer, Paulo Evaldo (2015)
This paper aims to problematize knowledge production in Physical Education (PE) from the Brazilian context. From a hermeneutic perspective, it questions the nature of its knowledge considering the difficulties arising from the objects/subjects diversity, methodological approaches and epistemological perspectives. From historic and controversial theory-practice relationship, it identifies some research problems of the area, since it is heiress of the Western dualism in its different aspects. We understand that overcoming the epistemological classical notion places us before other types of research and knowledge validation. It also recognizes that the autonomy enjoyed by science is a concession of a Democratic and Republican Society (therefore, it is always relative) and that it is constantly threatened by instrumental and political perspectives. With regards to intervention problems, we consider that they should occupy a prominent place inside research concerns, even if it means radicalize this interdisciplinary character of Physical Education. We concludes that in these disciplinary field boundaries, and with an effort to link them with pedagogical challenges, knowledge production can contribute to shape a Physical Education identity.